Combination tanning mechanism inspired environmentally benign catalyst for efficient degradation of tetracycline - Xiao, Meng (2023)
The utilization of chelation reaction between metals and tannins is a common tanning method in leather chemistry. Herein, a novel combination tanning mechanism inspired environmentally benign catalyst (CMBT-Fe0) was synthesized by immobilizing Fe nanoparticles onto bayberry tannin (BT) grafted chitosan microfibers (CM). The obtained catalyst featured a well-defined microfibrous structure, on which Fe0 nanoparticles were highly dispersed to exhibit exceptional catalytic activity for the degradation of tetracycline (TC). The catalytic activity of CMBT-Fe0 was 1.72 times higher than that of the commercial Fe0 nanoparticles without immobilization, with 95.03% of TC degraded within 90.0 min. The CMBT-Fe0 catalysts were recycled 6 times, with the removal rate of TC maintained at 82.56%. Furthermore, a possible mechanism responsible for the catalytic removal of TC was provided by analyzing the catalytic degradation products via liquid chromatography-mass spectrometry. Therefore, our investigation successfully developed efficient catalysts to address the concerned environmental issue of antibiotic pollution.